2020
DOI: 10.1016/j.jbo.2020.100323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of whole-body vibration exercise on physical performance and bone turnover in patients with monoclonal gammopathy of undetermined significance

Abstract: Highlights Whole-body vibration exercise improves physical performance in MGUS patients. Muscle strength and endurance are improved after WBV in MGUS. Whole-body vibration increases cortical bone mineral density in female participants. Bone biomarkers show an adaptive response of the bone in MGUS after WBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…In clinical settings, exercise training has already been proven to be feasible in patients suffering from MM [ 32 , 33 ]. We recently showed that whole-body vibration exercise benefits physical fitness and bone turnover in patients with monoclonal gammopathy of undetermined significance, a precursor condition of MMBD [ 29 ]. Based on our previous findings and the reports by Eda et al that a combination treatment of CC-292 with carfilzomib improved bone mass [ 10 ], we further reasoned that the combination of mechanical loading with CC-292 enhances the osteoprotective effect of physical stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical settings, exercise training has already been proven to be feasible in patients suffering from MM [ 32 , 33 ]. We recently showed that whole-body vibration exercise benefits physical fitness and bone turnover in patients with monoclonal gammopathy of undetermined significance, a precursor condition of MMBD [ 29 ]. Based on our previous findings and the reports by Eda et al that a combination treatment of CC-292 with carfilzomib improved bone mass [ 10 ], we further reasoned that the combination of mechanical loading with CC-292 enhances the osteoprotective effect of physical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Physical stimuli have a potent non-pharmacological anabolic effect as exercise enhances bone mass in the elderly [ 27 , 28 ]. Recently, we showed in a clinical study that whole-body vibration exercise is beneficial with respect to physical performance in patients with monoclonal gammopathy of undetermined significance, a precursor condition of MMBD [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration 2023, 6, FOR PEER REVIEW 3 In this review paper, we will summarize vibration studies involving cancer models (Figure 1) in clinical trials (Table 1) [51][52][53][54][55][56], in animal studies (Table 2) [57][58][59], and in vitro studies examining bone-cancer cell interactions (Table 3) [16,17,60]. We will also discuss various parameters that may affect vibration efficacy, including age, vibration settings, and differences between bone sites.…”
Section: Mechanical Stimulation and Specifically Vibrationmentioning
confidence: 99%
“…The effects of vibration on cancer patients (Table 1) [51][52][53][54][55][56], cancer animal models (Table 2) [57][58][59], and bone-cancer cell interactions (Table 3) [16,17,60] are summarized below (Figure 1). Specifically, we examine vibration safety, summarize vibration effects on bone health (i.e., BMD, bone volume, bone remodeling, and bone turnovers), and elucidate the impacts of vibration on tumor burden and progression, bone vascularization, and mesenchymal stem cells (MSCs).…”
Section: Vibration Effects On Cancer Models and Bone-cancer Cell Inte...mentioning
confidence: 99%
“…Most importantly, accounting for the small sample size of eight patients and the heterogeneous exercise participation and measurement procedure, either a large effect size or factors of chance and positive selection bias led to statistical significance. Recently, we demonstrated a highly significant improvement of physical activity and functioning in patients with the precursor condition monoclonal gammopathy of undetermined significance under whole-body vibration exercise training [28].…”
Section: Adherence and Efficacymentioning
confidence: 99%